The Relationship between Spiritual Intelligence and Emotional Intelligence with Learning Outcomes Akidah Akhlak Students in Madrasah Ibtidaiyah - Maruhawa, Umar Saleh; Zein, Achyar; Budianti, Yusnaili (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this study is to examine the relationship between Spiritual Intelligence and Emotional Intelligence and student learning outcomes in Akidah Akhlak subjects. This study used a quantitative method with a correlational research approach. The purpose of this correlation study is to determine whether or not there is a relationship between two independent variables and one quantitatively dependent variable. At a score of 4, the strength of the relationship between Spiritual Intelligence and Emotional Intelligence, both individually and collectively, with the Learning Outcomes variable in Akidah Akhlak subjects can be predicted. The study's findings indicate that there is a significant relationship between Spiritual Intelligence and Student Learning Outcomes in Akidah Akhlak subjects, with a significant contribution of 21.11 percent close relationship between learning outcomes. Spiritual Intelligence and Emotional Intelligence have a significant relationship with student learning outcomes in Akidah Akhlak subjects of 0.598, with a close relationship contribution of 35.8 percent. Based on the findings of this study, it is possible to conclude that Spiritual Intelligence and Emotional Intelligence, either individually or in combination, are two factors that are very significantly related to improving student learning outcomes in the Akidah-Akhlak subjects.